Pengaruh Pengeluaran Pemerintah, IPM, Pertumbuhan Ekonomi, dan Investasi terhadap Tingkat Pengangguran di Sulawesi Selatan Tahun 2017-2019 - Mirna Kuswiyati; Yuni Prihadi Utomo (Ekonomis: Journal of Economics and Business, 2022)
Unemployment is a case that is often lived by all countries, both in developing countries as well as developed countries. High and low levels of unemployment in a country will describe the good or bad economy of a country/region. In this study, it has the aim of observing various factors that have an impact on the unemployment rate in South Sulawesi in 2014-2019. The method used is the data panel data analysis, which includes data cross section 24 regencies/cities in South Sulawesi & Data Time Series 2017-1019. The final results of the study showed that the random effect model (brake) was chosen as the best estimated model. This estimated model exists, with the coefficient of determination (R2) of 0.8753. The level of unemployment in the Regency or City of South Sulawesi Province in 2017-2019 was apparently influenced positively by the variable economic growth & negatively by the investment variable, while the variable government expenditure and the human development index had no influence. The regression coefficient of economic growth which is far greater than the Investment Regression Coefficient, shows that in the Regency or City of South Sulawesi Province during 2017-2019, the pattern of economic development tends to be capital intensive, thus triggering unemployment. The Gowa, Palopo Jeneponto, Takalar and Bantaeng regions are 5 regions with the highest unemployment problem.